(untitled) (International Journal of Engineering and Computer Science, 2018)
the development of multimedia technology in Content Based Image Retrieval (CBIR) System is one of the prominent area to retrieve the images from a large collection of database. The feature vectors of the query image are compared with feature vectors of the database images to obtain matching images. It is practically observed that any one algorithm is not efficient in extracting all different types of natural images. Hence a thorough analysis of certain color, texture and shape extraction techniques are carried out to identify an efficient CBIR technique which suits for a particular type of images. The Extraction of an image includes feature description and feature extraction. In this paper, we proposed Color Layout Descriptor (CLD), Gray Level Co-Occurrences Matrix (GLCM), Marker-Controlled Watershed Segmentation feature extraction technique which extract the matching image based on the similarity of Color, Texture and Shape in the database. For performance analysis, the image retrieval timing results of the proposed technique is calculated and compared with each of the individual feature.